KOCHANOWSKI MALCZEWSKIEGO – KOCHANOWSKI NORWIDA - Skalińska, Ewangelina (Colloquia Litteraria, 2017)
The article deals with the reception of the Old-Polish and early Romantic literature in Norwid’s body of work. The author argues that when Norwid deals with Old-Polish literature, especially Jan Kochanowski’s texts, he mostly does it by evoking Antoni Malczewski’s poetic novel Maria.